Special educational needs and the global middle class: navigating local, national and global citizenship in the Middle East. Issue 1 (2nd January 2021) - Kiwan, Dina
ABSTRACT: This article examines the inter-relationships among citizenship, class and disability through the methodological juxtaposition of critical policy analysis of constructions of disability and an autobiographical sociology of global middle-class parental strategies in school admissions processes in the Middle East. The author advances the theoretical case that disability is mediated through class and citizenship, and she elucidates the role of affect in the construction of disability and its relation to citizenship. Recognising emotion as a social, cultural and political practice, she proposes that this, in turn, has implications for reclaiming affect in the production of new knowledge on disability and citizenship in the Middle East.